Exosomal miR‐21/Let‐7a ratio distinguishes non‐small cell lung cancer from benign pulmonary diseases. Issue 4 (11th June 2020) - Yang, Guofeng; Wang, Tao; Qu, Xiangyun; Chen, Shuchen; Han, Ziyang; Chen, Sui; Chen, Mingduan; Lin, Jihong; Yu, Shaobin; Gao, Lei; Peng, Kaiming; Kang, Mingqiang
Abstract: Aim: To assess the exosomal miR‐21/Let‐7a ratio, a noninvasive method, in distinguishing non‐small cell lung cancer (NSCLC) from benign pulmonary diseases. Methods: The exosomes were extracted from the peripheral blood serum using serum exosomal extraction kit. miR‐21 and Let‐7a levels were evaluated by quantitative reverse transcription polymerase chain reaction. Results: We found that miR‐21/Let‐7a ratio of NSCLC patients was significantly higher than that of healthy people, patients with pulmonary inflammation diseases, and benign pulmonary nodules, respectively. Receiver‐operating characteristic analysis revealed that as compared with healthy controls, miR‐21/Let‐7a produced the area under the curve (AUC) at 0.8029 in patients with NSCLC, which helped to distinguish NSCLC from healthy controls with 81.33% sensitivity and 69.57% specificity. In addition, the AUC of miR‐21/Let‐7a in NSCLC patients was 0.8196 in comparison to patients with pulmonary inflammation diseases. Meanwhile, the sensitivity and specificity were 56.00% and 100%, respectively. Furthermore, compared with patients with benign pulmonary nodules, the AUC of miR‐21/Let‐7a in NSCLC patients was 0.7539. The sensitivity and specificity were 56.00% and 82.61%, respectively. Conclusion: In the present study, our findings revealed that exosomal miR‐21/Let‐7a ratio holds considerable promise as a noninvasive biomarker for the diagnosis of NSCLC from benign pulmonary diseases.